Reliability and validity of 10-item Kessler Scale (K10) Chinese version in evaluation of patients with coronary heart disease (Kessler 10中文版量表在冠心病患者中应用的信效度检验) - YE Yumei (叶玉梅); ZHU Qian (毛芳莹); MAO Fangying (朱倩); HU Yaoyao (胡尧尧) (Journal of International Translational Medicine Limited, 2021)
Objective To test the reliability and validity of 10-item Kessler Scale (K10) Chinese version in patients with coronary heart disease (CHD), and to determine its application value in the field of CHD. Methods The convenience sampling method was adopted to select 110 patients with CHD as the research objects. The K10 was used to investigate the patients, and the reliability and validity of the scale was evaluated by item analysis, factor analysis and reliability test. Results Cronbach's α coefficient of the total was 0. 828, and Cronbach's α coefficient of each dimension was 0. 743 and 0. 816, respectively. The retest reliability of the total meter was 0. 732, and the retest reliability coefficients of factor 1 and factor 2 were 0. 714 and 0. 768. By exploratory factor analysis, two common factors were extracted, and the cumulative variance contribution rate was 59. 044%. Conclusion The scale has good reliability and validity in patients with CHD and can be widely used. (目的 检验Kessler 10量表在冠心病患者中的信效度, 以确定其在冠心病领域的应用价值。方法 采取便利抽样法, 选取某三级医院就诊的110例冠心病患者为研究对象, 使用Kessler 10量表对其进行调查, 对数据进行项目分析、因子分析和信度检验等, 评价该量表的信效度。结果 总量表的Cronbach's 系数为0. 828, 各个维度的Cronbach's 系数分别为0. 743、0. 816。总量表的重测信度为0. 732, 因子1、因子2的重测信度系数为0. 714、0. 768。探索性因子分析, 提取2个公因子, 累积方差贡献率为59. 044%。结论 Kessler10中文版量表在冠心病患者中的应用具有良好的信效度, 可以推广使用。)